Internationalizing Rural Science Teacher Preparation Action Research for Global Competency - Buck, Gayle A.; Dimitrieska, Vesna; Akerson, Valarie L. (Contemporary Trends and Issues in Science Education, 2023)
X, 299 p. 1 illus.